Challenging Habermas’ Practical Discourse to Justify the Rights of Animals - Nowak, Ewa; Ciereszko, Kinga; Dłużewicz, Alicja; Napiwodzka, Karolina (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The article is about to challenge Habermas’ practical discourse approach and to explore its potentials for the justification of animal rights. Firstly, the classic concepts of agential features are discussed to examine whether animal agents deserve their rights (quasi sui juris in terms of H. Jonas) or they should be unconditionally recognized as continuously present in and endangered by the human and social world (Sections 1, 2, 3). Secondly, the principle of universalization of rights employing practical discourse is revised and extended to create the most favorable communicative-discursive opportunity for advocating for animal rights and catalyzing an agreement upon their validity, to adopt them as a justified “new social norm”, and so to overcome the limitations of practical discourse. Subsequently, Habermas’ view on the rights of animals is discussed (Section 4). The authors try to contribute to the “therapeutic” discourse recommended by Habermas when the matter of practical discourse rises controversies.